2012
DOI: 10.1007/s10995-012-1103-y
|View full text |Cite
|
Sign up to set email alerts
|

Least Explored Factors Associated with Prenatal Smoking

Abstract: Objectives Poor pregnancy and birth outcomes are major problems in the United States, and maternal smoking during pregnancy has been identified as one of the most preventable risk factors associated with these outcomes. This study examines less explored risk factors of smoking among underserved African American pregnant women. Methods A cross-sectional survey was conducted at an outpatient obstetrics-gynecology clinic of an inner-city university hospital in Virginia from March 2009 through January 2011 in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Demographic characteristics of pregnant smokers in this review match those found in the literature for Black or African American (B/AA) and American Indian or Alaska Native (AI/AN) pregnant smokers (Brownson et al, 1992; Hickman, Delucchi, & Prochaska, 2010; Masho et al, 2013; Maxson et al, 2012; Nguyen et al, 2012; Orr et al, 2005; Orr, Blazer, & Orr, 2012; Pletsch, Morgan, & Pieper, 2003 for B/AA; Eichner et al, 2010; Geishirt-Cantrell et al, 2005; King et al, 1997 for AI/AN). Culturally specific characteristics have been also identified, that are unique to the B/AA and AI/AN populations, including stress based on experiences of racial discrimination (B/AA; Nguyen et al, 2012), tobacco sale as a major income venue (AI/AN; Hodge et al, 2004), and ceremonial significance of tobacco (AI/AN; Hodge & Struthers, 2006; King et al, 1997).…”
Section: Discussionsupporting
confidence: 62%
“…Demographic characteristics of pregnant smokers in this review match those found in the literature for Black or African American (B/AA) and American Indian or Alaska Native (AI/AN) pregnant smokers (Brownson et al, 1992; Hickman, Delucchi, & Prochaska, 2010; Masho et al, 2013; Maxson et al, 2012; Nguyen et al, 2012; Orr et al, 2005; Orr, Blazer, & Orr, 2012; Pletsch, Morgan, & Pieper, 2003 for B/AA; Eichner et al, 2010; Geishirt-Cantrell et al, 2005; King et al, 1997 for AI/AN). Culturally specific characteristics have been also identified, that are unique to the B/AA and AI/AN populations, including stress based on experiences of racial discrimination (B/AA; Nguyen et al, 2012), tobacco sale as a major income venue (AI/AN; Hodge et al, 2004), and ceremonial significance of tobacco (AI/AN; Hodge & Struthers, 2006; King et al, 1997).…”
Section: Discussionsupporting
confidence: 62%
“…ing during pregnancy [65]. Nicotine consumption was often also associated with concurrent consumption of alcohol and illegal drugs, either prior to or during pregnancy [51,58,62,65]. Pregnant women who smoked were also more likely to have an unplanned pregnancy [51,62,67] and these women also attended routine antenatal medical checkups less often or only in the advanced stage of pregnancy compared to non-smokers [32,35,61].…”
Section: Continued Next Pagementioning
confidence: 99%
“…Younger age, white ethnicity, not being religious, low socio-economic status, being nonimmigrant, performing less frequent antenatal consultation, null parity, husband alcohol consumption, previous history of alcohol and other illicit drugs use, unplanned pregnancy, lack of awareness about the harmful effects of alcohol on the fetus and peer pressure were the identified factors associated with alcohol consumption [35][36][37][38]. Being divorced, unemployed, younger age, low educational level and low socio-economic status, living with smoker, criminal history, working in receipt of social services, alcohol and illicit drug use, being fair to poor in perceived health, being previous heavy smoker, having at least one chronic disease and mental illness, and not having a regular medical doctor were the identified factors associated with cigarette smoking during pregnancy [35,[39][40][41][42]. Old age, living in mountainous region, being Islamic follower, and being smoker were identified as a risk factor for khat chewing during pregnancy [34,43,44].…”
Section: Introductionmentioning
confidence: 99%